Revaluasi Inventory dengan Menu Standard pada SAP-B1 Sesuaikah dengan IFRS - Eka Novianti (Binus Business Review, 2011)
Some available standard modules in SAP-B1 can be adapted for changes in accounting rules and regulations. One is the Inventory Revaluation menu of Inventory module. Users can use the menu to make Inventory value adjustments of value in SAP-B1, to be consistent with the values that must be presented in the financial statements. Based on the flexibility provided by SAP-B1menu, should not be too difficult for users of SAP-B1 to manage accounting transactions based on accounting rules that apply today, IFRS. IFRS requirements on inventory adjustment transactions with a value of SAP-B1 could be done more easily.